1993
DOI: 10.1007/bf00050722
|View full text |Cite
|
Sign up to set email alerts
|

Supply of phosphorus to the water column of a productive hardwater lake: controlling mechanisms and management considerations

Abstract: Onondaga Lake is a hypereutrophic, industrially polluted lake located in Syracuse, NY. High hypolimnetic concentrations of H2S that develop after anoxia restrict the accumulation of total Fe 2 + due to the formation of FeS, and may limit Fe-PO4 interactions. High water column concentrations of Ca 2 + and high rates of CaCO 3 deposition occur due to inputs of Ca 2 + from an adjacent soda ash manufacturing facility. Patterns of P concentration and other water chemistry parameters in the lower waters, and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Thirdly, Ca s / TP ratios were double those of Fe s /TP ratios in all three lakes (i.e. apatite solubility controls P release from sediments; Driscoll et al, 1993;Danen-Louwerse, Lijklema & Coenraats, 1995). Calcite precipitation as the controlling solid phase is consistent with in situ data from lakes treated with lime Reedyk et al, 2001) and with data from Gonsiorczyk, Casper & Koschel (1998) in a hardwater eutrophic lake in the Baltic region of Germany.…”
Section: Redox-insensitive Treatmentssupporting
confidence: 79%
“…Thirdly, Ca s / TP ratios were double those of Fe s /TP ratios in all three lakes (i.e. apatite solubility controls P release from sediments; Driscoll et al, 1993;Danen-Louwerse, Lijklema & Coenraats, 1995). Calcite precipitation as the controlling solid phase is consistent with in situ data from lakes treated with lime Reedyk et al, 2001) and with data from Gonsiorczyk, Casper & Koschel (1998) in a hardwater eutrophic lake in the Baltic region of Germany.…”
Section: Redox-insensitive Treatmentssupporting
confidence: 79%
“…Globally, the accumulation of phosphorus and particles with relatively lower content of calcium and silicon near the dams observed in the Lozoya system may be related to the pattern of sedimentation of fine particles. The notable Precipitation of calcium carbonate may be a process that removes dissolved phosphate from water through phosphate adsorption onto calcite particles or coprecipitation of phosphate-carbonate compounds (Driscoll et al 1993;Nurnberg 1998). However, the low values of sedimentary calcium observed in the Lozoya reservoirs as well as the opposite trends in P sed and Ca variation suggested that this process did not play any significant role in these reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…CARACO et al (1991) and PRAIRIE et al (2001) reported that more than half of 28 North American lakes exhibited an extremely low level of P release from sediment even after the onset of anoxia in the hypolimnion despite their variability in water chemistry, trophic states and geographical locations. Other workers observed none or delayed P release under anoxic conditions (e.g., SCHINDLER et al, 1977;DRISCOLL et al, 1993). The restricted flux from anoxic sediments might be explained by the resistance of Fe[III] minerals to reduction or by redox-insensitive binding mechanisms.…”
Section: Control Of Phosphorus Retention By Sediment Compositionmentioning
confidence: 92%